Pengembangan Instrumen Kecakapan Kerja Siswa Sekolah Menengah Kejuruan - Amirullah, Muhammad; Supriatna, Mamat (Program Studi bimbingan Konseling PPs UNM Makassar, 2018)
This research aims to develop the employability skills instrumen that will be used to measure the employability skills on vocational high school students. The method was used is a model of research and development. The instrumen developing is based on the results of the synthesis construct of employability skills theories. The sample were selected are 34 students of SMKN 13 Bandung. Based on the result of the research, it showed that the employability skills instrumen that was arranged had a good validity, shown by content validity with expert judgment and empiric validity with pearson product moment correlation. The reliability of the employability skills instrumen included an enough category that was shown by the high alpha reliability coefficient score that was 0.994